2002
DOI: 10.1002/ppul.10218
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and symptom perception in children with asthma and their parents

Abstract: A large proportion of children with asthma are managed without recourse to specialized care, and treatment decisions are based solely on symptoms as reported by the children and their parents. We investigated 90 school-age children with the diagnosis of asthma and their accompanying parent to evaluate whether we can obtain better information by using three different means of asking for asthma symptoms: a questionnaire for children (QSR(children)), "smilies," and a visual analogue scale for children (VAS(childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 35 publications
2
37
1
Order By: Relevance
“…This finding is similar to what others have suggested for report of daytime symptoms (Braun-Fahrlander et al, 1998;Fritz, McQuaid, Spirito, & Klein, 1996;Horak, Grassl, Skladal, & Ulmer, 2003;Lara et al, 1998);Mittal, Khanna, Panjabi, & Shah, 2006;Renzoni et al, 1999). Parents and children can be taught symptom specific identification skills, such as wheezing (Lee, Arroyo, & Rosenfeld, 1996), and this can be a focus of educational efforts, especially if the child has moderate-severe symptoms where inaccurate appraisal has had the greatest negative impact on control assessments (Halterman, 2006).…”
Section: Discussionsupporting
confidence: 81%
“…This finding is similar to what others have suggested for report of daytime symptoms (Braun-Fahrlander et al, 1998;Fritz, McQuaid, Spirito, & Klein, 1996;Horak, Grassl, Skladal, & Ulmer, 2003;Lara et al, 1998);Mittal, Khanna, Panjabi, & Shah, 2006;Renzoni et al, 1999). Parents and children can be taught symptom specific identification skills, such as wheezing (Lee, Arroyo, & Rosenfeld, 1996), and this can be a focus of educational efforts, especially if the child has moderate-severe symptoms where inaccurate appraisal has had the greatest negative impact on control assessments (Halterman, 2006).…”
Section: Discussionsupporting
confidence: 81%
“…These findings concur with earlier studies using mechanical PEF meters [27]. Some of these patients may be regarded as ''poor perceivers'', with few symptoms despite considerable variation in PEF and FEV1 and others as patients with excessive symptoms without any variation in PEF and FEV1 [28]. It would be interesting to see whether poor perceivers, identified by home recordings, could benefit from stepping up therapy, but this study was not designed to answer that question.…”
Section: Discussionsupporting
confidence: 62%
“…In most published guidelines, asthma severity classification involved the use of lung function parameter [7,20]. A previous study suggested in school-age children, reported symptoms by both the children and parent did not reliably correlate with lung function [21]. In another study, concordance between functional evaluation and clinical status was only found for moderate persistent asthma but not for intermittent and mild persistent asthma [22].…”
Section: Discussionmentioning
confidence: 99%